THE KYIV POSTER SCHOOL DURING THE PERESTROIKA PERIOD: VISUAL LANGUAGE AND CONTENT - Будник, А. В.; Сенега, Л. М. (Art and Design, 2021)
Purpose: to analyze the specifics of the Kyiv poster school of the Perestroika period. Methodology. Historical-comparative and art-scientific methods of analysis were used for the research. Results. The Perestroika period saw the final transformation of Ukrainian poster techniques and tools: from dogmatic system of Soviet school of visual arts to polystylistics of social, political, ecological and cultural posters at the time of fundamental social changes. Each of the major regional schools of the Ukrainian poster genre met the turning point of the era in accordance with its deeply rooted tradition or unconscious inertia. Appeal to the previously forbidden themes, repositioning of the theme of Ukrainianism in the poster, unexpected technical and artistic solutions, gravitating towards the smooth concepts of European poster movements – all this was presented and interpreted in terms of regional specificity. The attention of this study was focused on the Kyiv school. External and internal influences on the work of the Kyiv masters were analyzed. It was determined which themes were most often reflected in the posters and what were the stylistic changes. Scientific novelty. For the first time was covered the specifics of the Kyiv poster school and how it interacted with other poster schools in Ukraine. Practical significance. The study allows us to expand our knowledge about the activities and artistic features of the Kyiv school of posters during Perestroika. The findings can be used in further research of Ukrainian poster art.